The Influence of Occupational Health And Safety Practices on Organizational Commitment and Job Performance - Ei, Myo Myo; Ekowati, Dian; Agustina, Tri Siwi; Phyu, May Moe Pwint (Faculty of Education Universitas Negeri Malang, 2023)
The aim of this study is to examine the four aspects of workplace health and safety practices: Safety Procedures and Risk Management (SPRM), Safety and Health Rules (SAHR), Occupational Hazard Prevention (OHP), and Organizational Safety Support (OSS) on organizational commitment. Moreover, this study also explores the effect of organizational commitment on the job performance of employees. The sample for the present study consisted of 105 employees who work in construction industries which are located in Mandalay Division, Myanmar. The findings of this study show that the two dimensions of occupational health and safety practices namely: Safety and Health Rules (SAHR) and Organizational Safety Support (OSS) positive effects on organizational commitment that are significant whereas the two dimensions of occupational health and safety practices: Safety Procedures and Risk Management (SPRM) and Occupational Hazard Prevention (OHP) do not affect the organizational commitment of employees significantly. The result also indicated that organizational commitment has a positive and significant effect on the job performance of employees.